Household transmission and carriage of Shiga toxin-producing Escherichia coli (STEC) O145, Stx1c: a family report - Elif Okumuş; Aynur Karadenizli (The Turkish Journal of Pediatrics, 2025)
Background. Infections induced by Shiga toxin-producing Escherichia coli (STEC), especially non-O157 serogroups like O145, pose considerable public health risks. Household transmission is crucial in the dissemination of STEC, particularly in settings characterized by close interaction, such as extended families. This study examines a case of a 5-month-old infant with hemolytic uremic syndrome (HUS) attributed to stx1c-positive STEC and analyzes transmission patterns within the household.